Bicycle helmets and risky behaviour: A systematic review. (January 2019) - Esmaeilikia, Mahsa; Radun, Igor; Grzebieta, Raphael; Olivier, Jake
Highlights: The world's first systematic review of bicycle helmet use and risk compensation. 23 studies were identified from self-reported surveys, crash or experimental data. Most studies (n = 18) do not support risk compensation hypothesis. Mixed results were found in 3 studies and 2 studies supported hypothesis. Ten studies found helmet use associated with safer cycling behaviour. Abstract: A long-standing argument against bicycle helmet use is the risk compensation hypothesis, i.e., increased feelings of safety caused by wearing a helmet results in cyclists exhibiting more risky behaviour. However, past studies have found helmet wearing is not associated with risky behaviour, e.g., committing a traffic violation was positively associated with a lower frequency of helmet use. There is a lack of consensus in the research literature regarding bicycle helmet use and the risk compensation hypothesis, although this gap in knowledge was identified in the early 2000s. This is the first study to carry out a systematic review of the literature to assess whether helmet wearing is associated with risky behaviour. Two study authors systematically searched the peer-reviewed literature using five research databases (EMBASE, MEDLINE, COMPENDEX, SCOPUS, and WEB OF SCIENCE) and identified 141 unique articles and four articles from other sources. Twenty-three articles met inclusion criteria and their findings were summarised. Eighteen studies found no supportive evidence helmet use was positively associated with risky behaviour, while three studies provided mixed findings, i.e., results for and against the hypothesis. For many of these studies, bicycle helmet wearing was associated with safer cycling behaviour. Only two studies conducted from the same research lab provided evidence to support the risk compensation hypothesis. In sum, this systematic review found little to no support for the hypothesis bicycle helmet use is associated with engaging in risky behaviour.